Behind the digital veil: decoding the influence of HR training on information security awareness in Saudi Arabia - Ahmed M. Asfahani (Cogent Business & Management, 2024)
Amidst Saudi Arabia's digital transformation, this study investigates the impact of HR training on information security awareness in the finance and healthcare sectors. Grounded in an interpretivist paradigm, semi-structured interviews with 26 participants reveal HR's crucial role in fostering a security-aware culture and facilitating collaboration between HR and IT departments. Key findings highlight five main themes: organizational culture and approach, collaboration and communication, training and education mechanisms, measurement and feedback, and sectoral insights. The study addresses literature gaps by presenting a novel perspective on HR's role in information security, emphasizing the balance between security and individual rights. Despite sector-specific limitations, the research underscores the importance of collaborative cybersecurity efforts and suggests areas for future exploration, particularly in data consistency. This research provides valuable theoretical and practical implications for the evolving landscape of information security in Saudi Arabia, aligning with the nation's Vision 2030 goals.
Keywords: 650; Information security awareness; employee training; digital transformation; collaboration dynamics; data protection